Improvement of Knee Alignment and Function After Corrective Surgery for Hindfoot Deformity: A Report of 3 Cases. Issue 2 (12th April 2022) - Etani, Yuki; Hirao, Makoto; Ebina, Kosuke; Noguchi, Takaaki; Okamura, Gensuke; Tsuboi, Hideki; Miyama, Akira; Tsuji, Shigeyoshi; Kunugiza, Yasuo; Okada, Seiji; Hashimoto, Jun
Abstract : Case: Marked varus or valgus hindfoot deformities in 3 patients with ankle osteoarthritis or rheumatoid arthritis were treated by corrective surgery using total ankle arthroplasty or distal tibia oblique osteotomy. All cases achieved not only sufficient correction and satisfactory clinical/radiographic hindfoot improvement but also improvements in both knee alignment and function. Conclusion: Corrective surgery for hindfoot deformity can potentially change or improve ipsilateral knee alignment and function, representing an unexpected benefit of hindfoot realignment.